Exports, education spending, foreign direct investment, and growth in Malaysia - Yusoff, Mohammed (2008)
This paper examines the relationship among exports, foreign direct investment(FDI), education spending and Malaysia’s economic development using the cointegration technique, VECM, and the Granger causality test. The results suggest that the variables: GDP, exports, foreign direct investment and education spending are cointegrated. The estimated long-run relationship shows that exports, FDI and education expenditure could explain the variation in real GDP where they are significant at one percent level. The Granger causality test indicates that the exports, foreign direct investment and education expenditure cause economic growth where they are also significant at one percent level. These imply that the Malaysian export-oriented, liberal foreign direct investment and education development strategies have played important role in the development of Malaysian economy.